Considerations on heat transfer in parallel-plate channels with staggered fins - Perao L.H.* (2017)
© 2017 Trans Tech Publications, Switzerland.This work addresses heat transfer in channels fitted with heat-conducting fins inserted in both walls, transversally to the flow direction, in a staggered arrangement. Turbulent fluid flow and conjugate heat transfer are assumed in the simulations. The hydrodynamic (pressure coefficient) and thermal (Nusselt number) behavior of the heat exchanger is investigated for different values of fin thickness, inclination angle and blockage ratio. The simulations show that the geometrical parameters of the finned channel cause changes in the flow topology, which in turn leads to significant differences in pressure drop and heat transfer rate. It is observed that the fin blockage ratio imposes the greatest effect in the hydrodynamic and thermal problems, followed by the fin inclination angle and thickness.